Pengembangan Sistem Informasi Perpustakaan Menggunakan Metode Prototype - Yudha K; Krisna Widatama; Murhadi (Universitas Mercu Buana Yogyakarta, 2023)
SMK Muhammadiyah Purwodadi is a private school in Purworejo City which has library facilities as a support for teaching and learning activities and is a good school open to the latest innovations from information technology to support proper education. SMK Muhammadiyah Purwodadi still uses handwriting in library data processing. System the manual that is still running is not feasible in handling book procurement activities, book catalogs especially borrowing and returning books. In improving library services at SMK Muhammadiyah Purwodadi, a library information system was built using codeigniter. The information system development method uses the prototype method. The designed information system has the ability to manage member data, book data, and especially loan data and book return data. This information system can calculate the cost of late fees. The goal to be achieved in making a library information system is that it can be used for school libraries in order to meet the needs of using school library information systems as a tool to facilitate member services, search for book data, collect book collections, reporting systems, especially administration management of returns and borrowing collections. Purwodadi Muhammadiyah SMK school library books.